2006
DOI: 10.1021/jm060711t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis from Caffeine of a Mixed N-Heterocyclic Carbene−Silver Acetate Complex Active against Resistant Respiratory Pathogens

Abstract: The bis(N-heterocyclic carbene) (NHC) silver complex, 3, with a methyl carbonate anion was formed from the reaction of the iodide salt of methylated caffeine, 1, with silver (I) oxide in methanol. Attempts to crystallize this complex from a mixture of common alcohols and ethyl acetate led to the formation of an NHC-silver acetate complex, 4. The more direct synthesis of 4 was accomplished by the in-situ deprotonation of 1 by silver acetate in methanol. Complex 4 demonstrated antimicrobial activity against nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(190 citation statements)
references
References 39 publications
8
175
0
1
Order By: Relevance
“…2). As determined by curve fitting of the semilogarithmically transformed data, the 50% lethal dose of SCC1 in this model is 289 g/ml, which is 48-fold greater than the MIC 90 for all of the P. aeruginosa strains previously tested and 145-fold above the MIC for PA M57-15 (20).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…2). As determined by curve fitting of the semilogarithmically transformed data, the 50% lethal dose of SCC1 in this model is 289 g/ml, which is 48-fold greater than the MIC 90 for all of the P. aeruginosa strains previously tested and 145-fold above the MIC for PA M57-15 (20).…”
Section: Resultsmentioning
confidence: 91%
“…1C) is composed of silver complexed to a methylated caffeine carrier (Fig. 1B) (20). SCC1 and the methylated caffeine SCC1 precursor (Fig.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous development of novel resistancedisrupting antimicrobial drugs should therefore be a prime activity of industry and academia (Rex 2014). There is significant unexplored space for antimicrobial silver-based drugs (Mijnendonckx et al 2013;Oehninger et al 2013) and it has been suggested that carbene-silver acetates derived from methylated caffeine may have the stability and antibiotic activity to become drug candidates (Kascatan-Nebioglu et al 2006;Hindi et al 2008). This idea led to the development of more lipophilic benzyl-substituted imidazole-and benzimidazole-derived carbene-silver complexes showing activity against Gram-positive and Gram-negative bacteria (Hackenberg and Tacke 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 1 Log reduction of Salmonella Typhimurium and Salmonella Enteritidis was observed in raw ground chicken breast meat with coffee filtrate, 0.93 mg glyoxal, and 1 mg caffeine/g chicken (Maletta & Were, 2012). In vitro antimicrobial activity of caffeine was evaluated against several bacterial strains including Escherichia coli, Pseudomonas aeruginosa, pseudomonas fluorescens, and Staphylococcus aureus (Kascatan-Nebioglu et al, 2006;Ramanaviciene et al, 2003). Thus, the addition of caffeine as a natural antimicrobial to milk, juice, and various beverages has potential, as supported by these studies showing antimicrobial activities on pathogens.…”
Section: Discussionmentioning
confidence: 99%